Pengaruh Kesadaran Etis, Locus Of Control, Pengalaman Kerja Dan Komitmen Profesi Terhadap Perilaku Akuntan Sebagai Variabel Moderasi: (Studi Empiris Pada Kantor Akuntan Publik di Kota Semarang dan Solo) - Bagiartini, M Chindy Selvirawati; Nugroho, Arief Himmawan Dwi (Owner : Riset dan Jurnal Akuntansi, 2024)
This exploration was led planning to decide the impact of moral mindfulness, locus of control, work insight and expert obligation to bookkeeper conduct as a directing variable. The populace in this study is a public bookkeeping firm in Semarang and Solo. The testing method utilized by the analysts was to utilize comfort inspecting. This study included 121 respondents from public accounting firms in Semarang and Solo who were external auditors and included junior accountants, senior accountants, managers, and partners. The information examination method utilized in this study utilized various straight relapse investigation with the SPSS program apparatus. Accountant behavior is unaffected by ethical awareness, locus of control, or work experience, according to the findings of this study. Nevertheless, accountant behavior is influenced by professional commitment. Proficient Responsibility doesn't direct Moral Attention to bookkeeper conduct. Professional Commitment is not a moderation factor Locus of Control on accountant behavior. Work Experience does not moderate Ethical Awareness of accountant behavior.